Benzoyl and Pivaloyl as Efficient Protecting Groups for Controlled Enzymatic Synthesis of DNA and XNA Oligonucleotides. Issue 10 (9th September 2022) - Flamme, Marie; Katkevica, Dace; Pajuste, Karlis; Katkevics, Martins; Sabat, Nazarii; Hanlon, Steven; Marzuoli, Irene; Püntener, Kurt; Sladojevich, Filippo; Hollenstein, Marcel
Abstract: Controlled enzymatic synthesis is an alluring alternative to solid‐phase synthesis and polymerase‐mediated incorporation of nucleotides for the crafting of chemically modified, therapeutic oligonucleotides. While this approach has met some success for the elaboration of long, unmodified DNA sequences, very little research efforts have been dedicated to xeno nucleic acids (XNAs). Here, we have evaluated the possibility of using various 3'‐ O ‐blocking groups for controlled synthesis of locked nucleic acids (LNA). LNA nucleosides were equipped with protecting groups used in synthetic organic chemistry and were evaluated for their stability. The most promising candidates, benzoyl‐ and pivaloyl‐protected nucleosides, were converted to the corresponding nucleotides. The resulting modified nucleotides were shown to be accepted by various polymerases. While single incorporation events were observed in high yields, strong esterase activity of polymerases represents a lasting hurdle that needs to be overcome. Overall, this article represents an additional step towards the controlled enzymatic synthesis of LNA‐containing oligonucleotides and could be extended to other sugar or nucleobase modified nucleotides. Abstract : LNA nucleotides equipped with different 3'‐ O ‐blocking groups were evaluated for their compatibility with controlled enzymatic synthesis. Benzoyl‐ and pivaloyl‐protected LNA nucleotides were readily accepted by polymerases.